2020
DOI: 10.1111/eje.12621
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and prevention of ergonomic risk factors among dental students

Abstract: Introduction Dentistry is a high‐risk profession for the development of work‐related disorders. Dental students are also exposed to several risk factors. The goal of the study was to determine and localise musculoskeletal pain during dental work, afterwards to measure electromyography signals from the muscles groups mostly affected by the musculoskeletal pain. Study was done in order to provide possible suggestions for the most effective preventive measures of MS pain among dental students. Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…By using a validated posture assessment instrument, “Branson’s dental operator posture assessment instrument” (PAI), researchers found a strong prevalence of postural problems among dental students [ 12 ]. In 2020, a study analyzed the students’ muscle activity during dental work using electromyography and recorded the spinal tilt via an inclinometer; this revealed a high ergonomic risk during dental work due to back flexion of more than 20 degrees and unfavorable muscle activity of the neck muscles [ 33 ]. Furthermore, by using the Rapid Upper Limb Assessment (RULA), a study of dental students found that they were required to maintain a posture that can lead to muscle fatigue and pain [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…By using a validated posture assessment instrument, “Branson’s dental operator posture assessment instrument” (PAI), researchers found a strong prevalence of postural problems among dental students [ 12 ]. In 2020, a study analyzed the students’ muscle activity during dental work using electromyography and recorded the spinal tilt via an inclinometer; this revealed a high ergonomic risk during dental work due to back flexion of more than 20 degrees and unfavorable muscle activity of the neck muscles [ 33 ]. Furthermore, by using the Rapid Upper Limb Assessment (RULA), a study of dental students found that they were required to maintain a posture that can lead to muscle fatigue and pain [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stress affected dentist at the beginning of their career, even during their studies 47,48,49 . Increased workload, time constraints and some aspects of clinical training, were identified as the main stressors among dental students 50,51 .…”
Section: Stress In the Dental Professionmentioning
confidence: 99%
“…It has been observed that even during the study of dentistry, students are exposed to the stress and consequences it causes [47][48][49][50][51][52][53][54][55] . A study conducted by Dunalp and Stewart indicates that 38% of the surveyed dentists feel constant worry and anxiety 56 .…”
Section: Prevalence Of Stress Among Dentists and Recommendations For Its Reductionmentioning
confidence: 99%
“…The dentist’s chair may affect the dentist’s musculoskeletal health [ 25 , 26 , 27 , 28 ]. The backrest angle and shape should be suited for the dentists’ health and comfort, and the design should not burden the human body, especially with the dentist’s long-term use [ 29 , 30 , 31 ]. Additionally, smooth chair movement is required in the process of treatment, considering durability and noise.…”
Section: Introductionmentioning
confidence: 99%
“…The dental unit chair causes eye fatigue due to light [ 8 , 9 ]; should feature an appropriate size and angle of the patient seat [ 10 , 11 , 12 , 13 ], and the appropriate usability of the foot controller [ 14 , 15 ]; the water fountain and cuspidor should be convenient [ 16 , 17 ]; and there should be harmony between the monitor and the overall treatment system [ 21 , 22 ], as well as size and stability of bracket table and controller [ 23 , 24 ]. It is selected by various factors, including the overall design [ 29 , 30 , 31 ]. However, it is difficult for dentists to choose a suitable dental unit chair, considering all factors.…”
Section: Introductionmentioning
confidence: 99%